How best to measure discretionary ﬁscal policy? Assessing its impact on private spending - Agnello, Luca (2013)
We develop a novel empirical approach to assess the effect of discretionary ﬁscal policy on private spending consisting of three stages: 1) extract the discretionary component of ﬁscal policy by estimating a ﬁscal policy rule; 2) use the residuals of the ﬁrst-stage regression to investigate the existence of crowding-in and/or crowding-out effects both in the short and the medium term; and 3) condition the response of private spending on a set of country characteristics. We ﬁnd that an expansion in discretionary ﬁscal policy boosts growth in the short term, but is detrimental in the medium term. In addition, the empirical ﬁndings suggest that the effect of discretionary ﬁscal policy on private spending varies across regions and income groups, and depends on countries' economic characteristics such as the level of economic development, trade openness, government and country size.